Operating in an Opioid Crisis: A Temporal Analysis of Pain Medication Prescribing Practices in Plastic Surgery. Issue 3 (March 2023) - Hammond, Jacob B.; Hung, Penny; Chang, Yu-Hui H.; Rebecca, Alanna M.; Howard, Michael A.; Teven, Chad M.
Abstract : Background: In response to the opioid epidemic, the United States declared a public health emergency in 2017. We evaluated pain medication prescribing practices among plastic and reconstructive surgeons, assessing pain medication prescription rates and opioid-related mortality both nationally and regionally within the United States. Methods: A retrospective analysis of Medicare Part D prescriber data among plastic surgeons from 2013 through 2017 was conducted. Pain medications were categorized as opioid and nonopioid medications. Trends in surgeon prescribing habits were evaluated using the Cochrane-Armitage trend test. Results: A total of 708, 817 pain medication claims were identified: 612, 123 claims (86%) were for opioid pain medications and 96, 694 claims (14%) were for nonopioid pain medications. Total pain medication claims decreased from 44% of all medications in 2013 to 37% in 2017 ( P < 0.001). Opioid medications decreased from 37% of total medication claims to 32% ( P < 0.001). The overall opioid prescription rate fell from 1.53 claims per beneficiary in 2013 to 1.32 in 2017 ( P < 0.001). Nonopioid pain medications decreased from 7% in 2013 to 6% in 2017 ( P < 0.001); nonsteroidal anti-inflammatory drug claims increased by 44%. The prescription rate of nonopioid medications decreased from 2.40 claims per beneficiary in 2013 to 2.32 in 2017 ( P < 0.001). An overall increase in opioid-related mortality was observed. Trends in pain medication prescriptions varied significantly among US regions and divisions. Conclusions: Plastic surgeons are prescribing less opioids and relying more on nonopioid pain medications. Increased adoption of multimodal pain treatment approaches among surgeons is a likely explanation for this trend in face of the current opioid crisis.